Κ-Opioid Receptor Plasma Levels Are Associated With Sex and Diagnosis of Major Depressive Disorder But Not Response to Ketamine. Issue 2 (March 2023) - Quintanilla, Brandi; Medeiros, Gustavo C.; Greenstein, Dede; Yuan, Peixiong; Johnston, Jenessa N.; Park, Lawrence T.; Goes, Fernando S.; Gould, Todd D.; Zarate, Carlos A.
Abstract: Background: Preclinical evidence indicates that the κ-opioid receptor (KOR)/dynorphin pathway is implicated in depressive-like behaviors. Ketamine is believed to partly exert its antidepressant effects by modulating the opioid system. This post hoc study examined the following research questions: (1) at baseline, were there differences in KOR or dynorphin plasma levels between individuals with major depressive disorder (MDD) and healthy volunteers (HVs) or between men and women? (2) in individuals with MDD, did KOR or dynorphin baseline plasma levels moderate ketamine's therapeutic effects or adverse effects? and (3) in individuals with MDD, were KOR or dynorphin plasma levels affected after treatment with ketamine compared with placebo? Methods: Thirty-nine unmedicated individuals with MDD (23 women) and 25 HVs (16 women) received intravenous ketamine (0.5 mg/kg) and placebo in a randomized, crossover, double-blind trial. Blood was obtained from all participants at baseline and at 3 postinfusion time points (230 minutes, day 1, day 3). Linear mixed model regressions were used. Results: At baseline, participants with MDD had lower KOR plasma levels than HVs ( F 1, 60 = 13.16, P < 0.001), and women (MDD and HVs) had higher KOR plasma levels than men ( F 1, 60 = 4.98, P = 0.03). Diagnosis and sex had no significant effects on baseline dynorphin levels. Baseline KOR and dynorphin levels did not moderate ketamine's therapeutic or adverse effects. Compared with placebo, ketamine was not associated with postinfusion changes in KOR or dynorphin levels. Conclusions: In humans, diagnosis of MDD and biological sex are involved with changes in components of the KOR/dynorphin pathway. Neither KOR nor dynorphin levels consistently moderated ketamine's therapeutic effects or adverse effects, nor were levels altered after ketamine infusion. Trial Registration: NCT00088699 (ClinicalTrials.gov ).